Penyediaan Rumah Baca Masyarakat Sebagai Solusi Cerdas Mengawali Budaya Membaca - Muhammad Ridwan Basalamah; Mohammad Rizal (Universitas Lancang Kuning, 2020)
The people of Argoyuwono Village who are not well educated and have insufficient levels of economic capacity to send their children to higher levels of education, therefore, need the help of housing providers, to obtain information and assistance, this can lead to things that can be done to improve their standard of living. The method of this program is the provision of a reading house to give a new nuance and further and quality knowledge travel through books. The result of this program is that the people of Arguyuwono village are very happy with the existence of a reading house, because they believe that providing a reading house will be able to be a conducive place to build smart and superior generation in the village and this program is getting help from other parties, both from the village apparatus , Community leaders, teachers and also the general public.